Thrombocytosis in 715 Dogs (2011–2015). (12th September 2017) - Woolcock, A.D; Keenan, A.; Cheung, C.; Christian, J.A.; Moore, G.E.
Abstract : Background: Thrombocytosis is a hematologic abnormality in dogs that has been associated with various neoplastic, metabolic, and inflammatory conditions. Objective: To classify thrombocytosis in dogs based on severity and evaluate whether there are associations between severity and underlying disease processes. Animals: Seven hundred and fifteen dogs with thrombocytosis and 1, 430 dogs with normal numbers of platelets. Methods: Retrospective study. Medical records of dogs with increased (>500 × 10 3 /μL; thrombocytosis group) and normal (300–500 × 10 3 /μL; control group) platelet counts between 2011 and 2015 were reviewed. Dogs were characterized by severity of platelet increase and diagnosis. Diagnostic categories included neoplasia, endocrine disease, inflammatory disease, or miscellaneous. Results: A total of 1, 254 complete blood counts with thrombocytosis from 715 dogs were included in the study. Median platelet count in this population was 582 × 10 3 /μL (500–1, 810 × 10 3 /μL). No correlation between severity of thrombocytosis and diagnosis was identified. Causes of secondary thrombocytosis included neoplasia (55.7%), endocrine disease (12.0%), and inflammatory disease (46.6%). Immune‐mediated disease was common (22.2%), associated with frequent glucocorticoid administration, and had a significantly higher median platelet count (636 × 10 3 /μL [500–1, 262 × 10 3 /μL] versus 565 × 10 3 /μL [500–1, 810 × 10 3 /μL]) when compared to the other inflammatory processes ( P  < 0.001). The diagnoses in the thrombocytosis dogs differed significantly from the control population ( P  < 0.001). Conclusions and Clinical Importance: Thrombocytosis is commonly associated with carcinoma and immune‐mediated disease in dogs.